2023
DOI: 10.1177/15353702231151980
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Galectin-3 and H-FABP correlate with poor physical performance in patients with congestive heart failure

Abstract: Heart failure (HF) is often associated with compromised physical capacity in patients. However, it is unclear if established HF markers correlate with the physical performance of patients with congestive HF (CHF). We assessed the left ventricular end-systolic dimension (LVESD) and ejection fraction (LVEF) and, physical performance parameters, including short physical performance battery (SPPB), gait speed (GS), and handgrip strength (HGS) in 80 patients with CHF along with 59 healthy controls. Furthermore, lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…We recently reported the basic laboratory parameters and other phenotypic characteristics of these patients. 30 The echocardiographic investigations revealed significant LV chamber dilatation and LV contractile dysfunction in CHF patients with ischemic and non-ischemic heart failure (Table 1). The BMI was higher in both ischemic and non-ischemic CHF patients than in healthy controls.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We recently reported the basic laboratory parameters and other phenotypic characteristics of these patients. 30 The echocardiographic investigations revealed significant LV chamber dilatation and LV contractile dysfunction in CHF patients with ischemic and non-ischemic heart failure (Table 1). The BMI was higher in both ischemic and non-ischemic CHF patients than in healthy controls.…”
Section: Resultsmentioning
confidence: 95%
“…29 Recently, we have reported that the plasma levels of H-FABP and galectin-3 negatively correlate with the physical performance of patients with CHF. 30 However, it is unknown whether these HF markers have any associations with frailty in patients with CHF.…”
Section: Introductionmentioning
confidence: 99%
“…[53] CRP has also been extensively studied with CVDs. [54,55] Chronic low-grade inflammation, resulting in high CRP levels, contributes to the development of atherosclerosis and other related heart disorders. [56][57][58] Probiotics have been shown to reduce CRP levels, thus suggesting their potential to modulate the immune response and alleviate inflammation, thereby decreasing the occurrence of CVD.…”
Section: Predictive Biomarkers Of Cvdmentioning
confidence: 99%
“…Echocardiography was performed as previously described. 24 In brief, two-dimensional (2D) echocardiography was performed through an echocardiography system containing a 3 MHz phased probe (Apollo i700, Canon Medical Systems, Beijing, China). The standard guidelines of the American Society of Echocardiography were followed.…”
Section: Transthoracic Echocardiographymentioning
confidence: 99%